PERANCANGAN UI/UX APLIKASI PROJECT BASED LEARNING PADA MATA KULIAH PEMROGRAMAN WEB MENGGUNAKAN PENDEKATAN DESIGN THINKING - Ahmad Yusron Anshori; Adam Bachtiar (JATISKOM : Jurnal Aplikasi Teknologi Informasi dan Sains Komputer, 2024)
The advancement of information technology has transformed various aspects of life, including education. At the University of Mandalika Education, the web programming course has adopted the Project-Based Learning (PBL) method to enhance students' practical skills. This research aims to develop a Project-Based Learning (PBL) application using the Design Thinking approach to improve User Interface (UI) and User Experience (UX). The five stages of Design Thinking used are Empathize, Define, Ideate, Prototype, and Test. This research involves observations and interviews with users as well as testing using Quant UX. The test results show that the success rate of application features ranges from 85% to 100%, with user satisfaction reaching 97% for students and 100% for lecturers and administrators. This application is expected to increase learning motivation and facilitate the web programming learning process.